Outsourcing Public Services: Ownership, Competition, Quality and Contracting - Fredrik N. G. Andersson; Henrik Jordahl (Lund University, School of Economics and Management, Department of Economics, 2011)
We survey the literature on the effects of public sector outsourcing. Guided by theory, we systematically arrange services according to the type and magnitude of their contractibility problems. Taken as a whole, the empirical literature indicates that public sector outsourcing generally reduces costs without hurting quality. This is clearly the case for "perfectly contractible services" like garbage collection, but outsourcing often seems to work reasonably well also for some services with more difficult contracting problems, e.g. fire protection and prisons. Outsourcing seems to be more problematic for credence goods, with residential youth care as the prime example. In contrast to previous reviews, we conclude that ownership and competition appear to be about equally important for the consequences of public sector outsourcing.
Keywords: D23; H11; L33; 330; outsourcing; contracts; tendering; ownership; competition; quality